Diet and feeding behaviour of longnosed skate Dipturus oxyrinchus - Mulas Antonello; Bellodi Andrea; Cannas Rita; Cau Alessandro; Cuccu Danila; Marongiu Martina Francesca; Porcu Cristina; Follesa Maria Cristina (Journal of Fish Biology, 2015)
A total of 255 longnosed skate Dipturus oxyrinchus caught in Sardinian waters (central-western Mediterranean Sea), was analysed with respect to fish total length (LT), season and depth, in order to provide information on diet and feeding behaviour. Specimens ranging from 93 to 1153mm LT, were collected at depths between 121 and 671 m, during experimental trawl surveys carried out from 2005 to 2010. The diet comprised crustaceans [prey specific index of relative importance (%IPSRI)=72⋅69], teleosts (%IPSRI =10⋅28) and molluscs (%IPSRI =10⋅94). Levins’ index (Bi) showed a narrow niche breadth (Bi =0⋅35). The mean±s.e. trophic level (TL) was 3⋅63±0⋅50. The analysis showed major ontogenetic changes in the feeding behaviour. Early life stages were characterized by a benthic diet, which changed to benthopelagic during growth. Mysids, particularly Lophogaster typicus (%IPSRI =34⋅51), were the main prey items of immature individuals, replaced by euphausiids, mainly Meganyctiphanes norvegica (%IPSRI =13⋅19), in maturing fish. Crustaceans became less important in mature specimens, being replaced by molluscs (%IPSRI =28⋅99) and teleosts (%IPSRI =24⋅56). A concomitant increase of the TL was recorded (mean±s.e.=3⋅41±0⋅44, 3⋅75±0⋅54 and 4⋅28±0⋅61 for immature, maturing and mature individuals). These feeding patterns ensured low levels of intraspecific competition. This study provides new information about the role that the D. oxyrinchus plays in the marine food chain and data now essential to formulate new and effective management plans for this species.